Retinal pigment epithelial detachment : differential diagnosis and therapy - Gamulescu, Maria-Andreea; Helbig, Horst; Wachtlin, Joachim (Springer, 2017)
This excellently illustrated book offers detailed guidance on the differential diagnosis and therapy of detachment of the retinal pigment epithelium (PED), a frequently seen feature in various diseases of the eye, including age-related macular degeneration and its subtypes, central serous chorioretinopathy, and systemic disorders. Introductory chapters discuss the anatomy, pathophysiology, and imaging of PEDs, highlighting how especially the increasing use of spectral domain OCT enables even small PEDs to be detected and followed over time. The diverse forms of PED are then described, with explanation of how they may hint at the underlying pathology or even be pathognomonic when considered in conjunction with other clinical features. New insights are provided into the characteristics of the various forms of PED, and predictors of complications - such as rip of the PED - are discussed. It is clearly explained how knowledge of the different types of PED and their underlying diseases can assist in creating an appropriate individualized follow-up and therapy scheme for each patient.